PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV SEKOLAH DASAR - Yenes Eri Kusuma, Iche Luxi; Putri, Dya Ayu Agustiana; Sari, Eka Yuliana (Educational Technology Journal, 2025)
This study investigates the impact of Quizizz as a learning media on the interest of fourth-grade elementary school students in Indonesia. Utilizing a quantitative survey method, data were collected through questionnaires administered to 37 students. The results indicate a significant positive effect of Quizizz on student interest in learning, with statistical analysis revealing a p-value of less than 0.001. The findings highlight the importance of engaging and interactive learning media in enhancing student motivation and participation in the learning process. This suggests that incorporating innovative educational tools like Quizizz can effectively improve students' interest and outcomes in their studies.